2021
DOI: 10.1002/smll.202104975
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Controlled Synthesis and Quasi‐Static Dielectric Resonances in Silver Iron Sulfide (AgFeS2) Nanocrystals

Abstract: Ternary metal‐chalcogenide semiconductor nanocrystals are an attractive class of materials due to their tunable optoelectronic properties that result from a wide range of compositional flexibility and structural diversity. Here, the phase‐controlled synthesis of colloidal silver iron sulfide (AgFeS2) nanocrystals is reported and their resonant light–matter interactions are investigated. The product composition can be shifted selectively from tetragonal to orthorhombic by simply adjusting the coordinating ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Notably, the UV-vis absorption spectrum of magnetite displayed an absorption band spanning 340-430 nm. Consistently, the band gap of magnetite NPs was identified at approximately 2.2 eV, corroborating findings from earlier research [29]. Dopant atoms (Ni and Zn) in the crystal lattice of a material can significantly influence its electronic structure, including the band gap.…”
Section: Optical Studiessupporting
confidence: 89%
“…Notably, the UV-vis absorption spectrum of magnetite displayed an absorption band spanning 340-430 nm. Consistently, the band gap of magnetite NPs was identified at approximately 2.2 eV, corroborating findings from earlier research [29]. Dopant atoms (Ni and Zn) in the crystal lattice of a material can significantly influence its electronic structure, including the band gap.…”
Section: Optical Studiessupporting
confidence: 89%
“…6,10 Hence, the plasmon-like features in the transient absorption spectra actually originate from the unique IB band structure of the Cu 3 VSe 4 NCs which enables Frölich resonance and leads to a quasi-static dielectric resonance in the visible region. 43,44 IB semiconductors such as CuFeS 2 , CuAgS 2 , and Cu 3 VS 4 have been reported to possess dielectric resonance. Gaspari et al proposed that IB semiconductors do not show divergences in the dielectric response, and are therefore natural epsilon-near-zero materials over a wide spectral region.…”
Section: Resultsmentioning
confidence: 99%
“…[55] Third, Yao et al reported that the SPR can be controlled by controlling the stoichiometry of iron atoms. [62] Finally, Lee et al have observed a very similar SPR-like feature for AgFeS 2 NCs, [71] but both these effects and the variation of iron stoichiometry are not currently fully understood.…”
Section: Surface Plasmonmentioning
confidence: 99%
“…[ 62 ] Finally, Lee et al. have observed a very similar SPR‐like feature for AgFeS 2 NCs, [ 71 ] but both these effects and the variation of iron stoichiometry are not currently fully understood.…”
Section: Optical Propertiesmentioning
confidence: 99%